Sistem Informasi Peminjaman Buku di Perpustakaan SD Islam Ulil Albab Kebumen Berbasis Web - Zulfikar Alie, Muhammad; Aprilia Sumarsono, Ferdynan; Nasirudin, Mukhamad; Waluyo, Ari (JASATEC : Journal Students Of Automotive, Electronic and Computer, 2021)
The library at SDI Ulil Albab is one of the libraries that still applies a manual system in data management, so it takes a lot of time in data management and book data search as well as the possibility of errors in recording transactions or calculating fines. On the basis of this, in this research, a web-based library information system is designed which aims to facilitate access to library data anywhere and anytime. The library information system design method in this study uses the waterfall method, where each stage must be carried out systematically. The programming language used in this library information system is PHP with CodeIgniter framework and MySQL database. After going through the stages of analysis, design, writing program code, testing and implementation, the library information system is ready to be used and accessed through the temporary page sdi-ulil-albab.my.id. The web-based library information system that has been built can streamline and streamline the book data management process at the SDI Ulil Albab Kebumen library.